Pengaruh Minat Masyarakat, Transparansi dan Platform Digital Terhadap Kewajiban Ziswaf di Jawa Barat - Suryaman, Maman; Athoillah, Mohammad Anton; Solehudin, Ending; Setiawan, Iwan (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2023)
Zakat, infaq and alms are a form of worship that is not only vertical or a form of obedience to Allah SWT, but also a form of worship that is horizontal or social humanitarian relations. The realization of the collection of zakat, infaq and sadaqah funds is still far away when compared to the potential of zakat, infaq and sadaqah funds in West Java. This study aims to determine the influence between public interest, transparency and digital platforms on the obligation of zakat, infaq and sadaqah in West Java Province. This study uses a verification descriptive method using public interest, transparency and digital platforms as research variables. The research was conducted with a quantitative approach with 125 respondents obtained by non-probability sampling technique in the form of accidental sampling. Data analysis was carried out by multiple linear regression analysis using supporting applications, namely SPSS for Windows version 26.0. The results of the study obtained the conclusion that partially there is a positive and significant influence between Public Interest on the Obligation of Zakat, Infaq and Sadaqah with the value of t count> t table (9.404> 1.979) with a significance value of 0.000 smaller than 0.05. Transparency of Management of Amil Zakat Institutions on the Obligation of Zakat, Infaq and Sadaqah with the value of tcount> t table (9,253> 1,979) with a significance value of 0.000 smaller than 0.05. Digital Platform on the Obligation of Zakat, Infaq and Sadaqah with a tcount> ttable value (11.312> 1.979) with a significance value of 0.000 smaller than 0.05. While simultaneously public interest, transparency and digital platforms have a significant influence on the obligation to pay Zakat, Infaq and alms. This is evidenced by Fcount> Ftabel, namely 70.071> 2.68, meaning that there is a significant influence between Public Interest, Transparency of Management of Amil Zakat Institutions and Digital Platforms on the Obligation to Pay Zakat, Infaq and Sadaqah. Furthermore, the R square value or the Coefficient of Determination has a value of 0.626, which means that there is a relationship between the relationship between Public Interest, Transparency and the Use of Digital Platforms on the Obligation to Pay Zakat, Infaq and Sadaqah as the dependent variable of 62.6% while 37.4% is influenced by other variables not examined in this study.